Pattern of antibiotic sensitivity of bacteria causing urinary tract infection in a private medical college hospital in Dhaka (Bangladesh Journal of Medical Science, 2015)
Background: Urinary tract infections (UTI), being the most common infections diagnosed in community and hospital, are to be treated scrupulously considering the type of infecting organism and its antibiotic sensitivity and resistance pattern. Aims and objectives: The aim of the present study was to observe the antibiotic sensitivity pattern of isolated uropathogens from urine samples of patients attending at Shahabuddin Medical College & Hospital, Dhaka, during the period of July 2008 to June 2009. Result: A total of 555 urine samples were studied; of which 84 (15.13%) were culture positive. Among 84 culture positive cases, 84 isolates were identified. Among the isolates, E.coli was the most predominant 61 (62.88%) followed by Enterococci 11 (11.34%), proteus 4 (4.13%) and Pseudomonas 3 (3.09%). Whereas Staphylococcus saprophyticus and Klebsiella showed frequency rate of 2 (2.06%) for each. However Gram positive cocci showed lowest frequency rate of 1 (1.03%). All of the isolates were sensitive to Netilmicin. The majority of isolates were sensitive to Imipenam (92.3%) followed by Amikacin (91.1%), Meropenam (83.3 %), Tetracycline (70%). Sensitivity & resistance rate were same (50%) in Vancomycin & Cefodoxime. Where complete (100%) resistance was shown to Ampicillin, Azithromycin and Cefoxitin. However all isolates were poorly sensitive to cotrimoxazole (35.7%), ciprofloxacin (43%) and nitrofurantoin (44.8%). Conclusion: So, routine urine culture and susceptibility before therapy should be encouraged and periodic evaluation of predominant organisms and their antimicrobial susceptibility pattern should be studied for appropriate selection of antibiotic for effective management of UTI cases.DOI: http://dx.doi.org/10.3329/bjms.v14i1.21562 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.70-74